RINTISAN DAN INOVASI TANAMAN OBAT DAN JAMU PADA KELOMPOK WANITA TANI DI GAMPONG BLANG PULO - Meliza, Richa; Chalid, Ibrahim; Kamil, Ade Ikhsan; Mujiburrahman, Mujiburrahman; Ilham, Iromi; Riski, Aflia; Al Usrah, Cut Rizka; Rangkuty, Rakhmadsyah Putra; Fitri, Dwi (Universitas Malikussaleh, 2025)
This research aims to explore the pilots and innovations in medicinal plant cultivation and herbal medicine making by the Women Farmers Group in Gampong Blang Pulo. The program aims to empower women through increasing skills and income, as well as introducing sustainable traditional medicine methods. In its implementation, the farmer women's group was given training on medicinal plant cultivation techniques and how to process them into market-ready herbal medicine products. The results showed an improvement in the local economy, strengthening the capacity of group members, and increasing community access to traditional medicine. In addition, this activity also contributed to the preservation of traditional knowledge about medicinal plants in the community. Another positive impact was the establishment of a wider social network and better environmental awareness among group members. However, there are challenges in terms of product marketing and group management that require further attention. Overall, these pilots and innovations have made a significant impact in empowering women and improving community welfare in Gampong Blang Pulo.